Global software development technical, organizational, and social challenges. - Lanubile, Filippo
The International Workshop on Global Software Development was held in Portland (Oregon, USA) on May 9 2003, as part of the International Conference on Software Engineering 2003. A multicultural group of twenty-five people contributed to a successful workshop that debated the continued challenges of software development in global teams. The workshop consisted of an invited talk, sixteen short presentations, and fruitful discussions. We present an overview of the workshop motivation and then focus on the workshop's technical program. The workshop web site, including papers and slides, can be found at <http://gsd2003.cs.uvic.ca>.
Keywords: Collaboration between distant sites; Dispersed software teams; Global software development